Georges Bataille og det hellige - introduktion til heterologien - Petersen, Hans Alstrup (Religionsvidenskabeligt Tidsskrift, 1985)
This article presents the French author and philosopher, whose heterology has had a decisive influence on the development of French text theory during the last decades. The point of departure is taken in Bataille’s analysis of the cave paintings in Lascaux, where the fundamental theme of prohibition and transgression is identified. Bataille’s reflections on economy follow thereafter, where economy is not centred on production and the circulation of wealth, but on the destruction, squander and sacrifice of the “accursed part” of economy: the place of religious, aesthetic and erotic activities in the general economy of social life. The “inner experience” which accompanies participation on these socially organized transgressions is treated in more detail in a section on religious sensitivity and its contradictory position at the borderline of prohibition and transgression. The problem is summed up in the conception of the heterogen (sacred) body: an “object” which is simultaneously rejected and incorporated into the social system of meaning. The article concludes with a text-theoretical discussion as an extension of Bataille’s parallel etween sacrifice and literary narrative.